On the HBO mechanism of X-ray neutron star - Zhang, C. M. (World Scientific Publ Co Pte Ltd, 2001)
We ascribe the 15-60 Hz Quasi Periodic Oscillation (QPO) to the periastron precession frequency of the orbiting accreted matter at the boundary of magnetosphere-disk of Xray neutron star (NS). Considering the relativistic motion mechanism for the kHz QPO, that the radii of the inner disk and magnetosphere-disk of NS are correlated with each other by a factor is assumed. The obtained conclusions include: all QPO frequencies increase with increasing the accretion rate. The theoretical relations between 15-60 Hz QPO (HBO) frequency and the twin kHz QPOs are similar to the measured empirical formula. Further, the better fitted NS mass by the proposed model is about 1.9 solar masses for the detected LMXBs.